The evolution of the housing sector in Saudi Arabia - AlJerbi, AbdulHamed Saeed (Journal of Economic, Administrative and Legal Sciences, 2019)
In this research we aim first to list the most important economical housing development factors and the most effective and decision makers in the Kingdom of Saudi Arabia, which emerges clearly in the reports of development plans that’s published by the ministry of economics and planning using the descriptive examination pattern that helps planning or investment authorities to build an image of the evolution of the sector and the Real Estate Sector Developers. We handled in the introduction the beginning of change and the evolution of urban housing through the steps of the Five -year plans since 1970. Then we based our study on the Publications and reports of the Five -year plans since the beginning of urban planning that started at 1970. in witch the researcher presumed it to be the Primary collimator for growth in the residential sector. With infuses on the reports of the Tenth Five -year plan which started at 2015 and which have been named (the challenge stage) by the Council of Economic and Development Affairs and in the script of the housing plan until 2020 within Saudi Arabia’s Vision program 2030. In conclusion, the paper recommended the infuses on the urban housing, and advantage from the governments’ orientation towards local and international investors. and at the same time the paper recommended steering clear from the idle land’s speculation.